Implementasi Kebijakan Pendidikan Full Day School di SMP-IT Nurul Ilmi - Muhammad Iqbal; Liza Nurfadillah; Ayu Rahmini Hia; Suri Lestari Br. Purba; Ahmad Naufal (Departement of Mathematics Education, 2023)
This study aims to describe 1) Implementation of the Full Day School policy carried out at SMP-IT Nurul Ilmi Medan Estate; 2) The problems faced at SMP-IT Nurul Ilmi Medan Estate in implementing the Full Day School; 3) Solutions made in solving the problem of implementing the Full Day School policy at SMP-IT Nurul Ilmi Medan Estate. The research method used is qualitative research with descriptive methods. Data obtained through interviews, observation, and documentation studies. The results of this study indicate that the implementation of the Full Day School policy has been carried out based on the Character Education Strengthening Policy made by the Ministry of Education of the Republic of Indonesia. Problems that arise during the implementation of Full Day Schools include inadequate facilities and infrastructure, adaptation of teachers, employees and students which takes a relatively long time, concerns parents of students for their children who are in grades 7 and 8 and adjustments to school schedules and student activities outside of school that have been previously scheduled. The solution taken by the school with existing problems is to always socialize student activities in the Full Day School policy, provide dispensation for students who have previously scheduled activities outside of school, carry out weekly evaluations and collaborate with institutions that can support Full Day School activities in schools.